Inquiry into the challenges of translating idioms extracted from musical lyrics - Andayani, Andayani; Herman, Herman; Syathroh, Isry Laila; Fatmawati, Endang; Syahrul, Ninawati; Al-Awawdeh, Nabil; Batubara, Junita; Saputra, Nanda (Research Journal in Advanced Humanities, 2023)
Translation has always been described as an age-long activity that impacts the communication between speakers of different languages. An aspect of translation that has remained evasive is the translation of idioms, mainly idioms that are tied to contextual peculiarities. Generally, idioms have enabled language users to transmit ideas that mirror how they think and their perspectives on specific scenarios. Translation also represents a time-honored practice of presenting content initially written in one language in another. Idiom translation is a specialized field since it calls for in-depth familiarity with various cultural notions in the target language and the source language. This research considered several factors crucial in translating idiomatic expressions extracted from musical lyrics. The focus was to explicate the challenges faced by translators in reproducing the meanings of idioms in musical contexts in one language into another without distorting or entirely omitting the intended meanings of the idioms when translated into the target language. The study critically examined the challenge of adopting appropriate technique or strategy, the challenge of encapsulating the internal semantic compositions of the idioms, the challenge of transmitting the social, cultural, stylistic, and contextual projections of the idioms, and the challenge of generating connecting expressions in the target language to match the disintegrated nature of musical lyrics. The result of the study further expounds on the importance of the in-depth knowledge of the translator, both in the two languages and like language use in music. Translators also need to explore diverging methodological approaches and employ diverging techniques when translating idioms in musical lyrics. The study further recommended using self-generated techniques and conceptual alignment to produce suitable equivalents of idioms extracted from musical lyrics in the target language.